2003
DOI: 10.1111/1469-8986.00075
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in behavioral and event‐related brain responses associated with response preparation and inhibition in a go/nogo task

Abstract: The present study investigated developmental trends in response inhibition and preparation by studying behavior and event-related brain activity in a cued go/nogo task, administered to nine-year-old children and young adults. Hits, false alarms, inattention, and impulsivity scores and ERP measures of inhibition (fronto-central nogo-N2 and P3), target selection (parietal go-nogo P3 difference), and response preparation (contingent negative variation; CNV) were collected. Higher false alarm and impulsivity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
177
7
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(229 citation statements)
references
References 38 publications
41
177
7
4
Order By: Relevance
“…It should be noted, however, that their findings of a larger P3a in children than in adults is not consistent with other reports in the literature (e.g., Oades et al, 1997). Jonkman et al (2003) examined age effects in ERPs elicted in a visual warned go/no-go task, the Continuous Performance Test (CPT-AX), in which letters are presented one at a time. The participants were instructed to press a button when the letter X appeared, but only when it was preceded by the letter A (AX sequence).…”
Section: Normal Developmentcontrasting
confidence: 59%
“…It should be noted, however, that their findings of a larger P3a in children than in adults is not consistent with other reports in the literature (e.g., Oades et al, 1997). Jonkman et al (2003) examined age effects in ERPs elicted in a visual warned go/no-go task, the Continuous Performance Test (CPT-AX), in which letters are presented one at a time. The participants were instructed to press a button when the letter X appeared, but only when it was preceded by the letter A (AX sequence).…”
Section: Normal Developmentcontrasting
confidence: 59%
“…P1 was defined as a positive deflection between 60 and 150 ms, and P3 was defined as the positive deflection between 310 and 610 ms. The time windows were determined after considering previous studies with similar age groups (Ciesielski et al, 2004; Davis et al, 2003; Jonkman et al, 2003; Lahat et al, 2010) and visual examination of the grand averaged and individual waveforms. Peak latency and mean amplitude measures were averaged across electrodes within clusters selected to be compatible with the 10–20 electrode placement system.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies have found ERPs modulated by response inhibition demands were more evident at posterior electrode sites (Brydges, Anderson, Reid, & Fox, 2013; Ciesielski et al, 2004; Durston et al, 2002; Jonkman et al, 2007). Jonkman, Lansbergen, and Stauder (2003) directly compared 9-year-old children and adults, and found that the No-go P3 was maximal at posterior electrode sites in children, but frontally maximal in adults. Furthermore, several studies have found laterality differences in brain activity during response inhibition between children and adults.…”
mentioning
confidence: 99%
“…'X') appears. In the cued variant of the go/nogo task (Band, Ridderinkhof, van der Molen, 2003;Bekker, Kenemans & Verbaten, 2004;Bruin, Wijers, & van Staveren, 2001;Jonkman, Lansbergen & Stauder, 2003;Randall & Smith, 2011;Smith, Jonstone & Barry, 2006), a cue provides information about which response is probably required and subjects are asked to prepare this response (a key press with a left finger, a right finger, or no response). Whether or not the cued response is subsequently required is clarified by a second stimulus that follows after a variable delay.…”
Section: The Stop-signal and Go/nogo Paradigmmentioning
confidence: 99%